Children’s Pronoun Interpretation Problems Are Related to Theory of Mind and Inhibition, But Not Working Memory - Kuijper, Sanne J. M.; Hartman, Catharina A.; Hendriks, Petra (Frontiers in Psychology, 2021)
In several languages, including English and Dutch, children’s acquisition of the interpretation of object pronouns (e.g., him) is delayed compared to that of reflexives (e.g., himself). Various syntactic and pragmatic explanations have been proposed to account for this delay in children’s acquisition of pronoun interpretation. This study aims to provide more insight into this delay by investigating potential cognitive mechanisms underlying this delay. Dutch-speaking children between 6 and 12 years old with autism spectrum disorder (ASD; n=47), attention-deficit/hyperactivity disorder (ADHD; n=36) or typical development (TD; n=38) were tested on their interpretation and production of object pronouns and reflexives and on theory of mind, working memory, and response inhibition. It was found that all three groups of children had difficulty with pronoun interpretation and that their performance on pronoun interpretation was associated with theory of mind and inhibition. These findings support an explanation of object pronoun interpretation in terms of perspective taking, according to which listeners need to consider the speaker’s perspective in order to block coreference between the object pronoun and the subject of the same sentence. Unlike what is predicted by alternative theoretical accounts, performance on pronoun interpretation was not associated with working memory, and the children made virtually no errors in their production of object pronouns. As the difficulties with pronoun interpretation were similar for children with ASD, children with ADHD and typically developing children, this suggests that certain types of perspective taking are unaffected in children with ASD and ADHD.